Caroline Walker Bynum: Historian of Fragments - Galea, Kate (Toronto journal of theology, 1995)
This article attempts to introduce the work of Caroline Walker Bynum by presenting the evolution of her thought through more than two decades of publication. For those unfamiliar with her work, the summaries presented below will serve as an introduction to one of the more brilliant scholars of this generation. For those who have met Bynum's work, the interest will lie in following the development of her thought and tracing both the common threads and the differences through the sixteen articles and four books under examination here.